Surveying and resonating with teacher concerns during COVID-19 pandemic - Phillips, Louise Gwenneth; Cain, Melissa; Ritchie, Jenny; Campbell, Chris; Davis, Susan; Brock, Cynthia; Burke, Geraldine; Coleman, Kathryn; Joosa, Esther (Teachers and teaching, theory and practice, 2024)
The COVID-19 pandemic jolted teachers to the front line of complex, under resourced negotiation of quality distance learning, whilst also being key communicators with students and families about how to be COVID safe. Media reports debated preschool and school closures and child safety, but scarcely considered teachers. Motivated by the silencing of teachers and extraordinary changes to education, we gathered as a group of nine educational researchers located in Australia, New Zealand, Singapore and U.S.A to create a survey platform for teachers' lived experiences of the impact of COVID-19. Our survey asked 22 questions and attracted 624 responses. This article focuses on question 12: What are the issues you are struggling with and need support with? Drawing from Latour's provocation we distil key 'matters of concern' from the data, illustrated by excerpts from teacher responses and echoed by the authors' COVID lived experiences as interwoven blackout poetry. Our collated experiences highlight struggles with online learning, connectivity/communication with students and families, quality of teaching, and workload, and the need to value and invest in education and the professionalism of teachers to address these struggles.